Management of pregnancy and lactation. Issue 6 (December 2018) - Sammaritano, Lisa R.; Bermas, Bonnie L.
Abstract: Management of pregnancy in patients with rheumatic and musculoskeletal disorders is both challenging and rewarding. Most patients with rheumatic disease can have a successful pregnancy. Pregnancy outcome is improved when maternal autoimmune disease is stable or quiescent. Prepregnancy evaluation and counseling is important to identify risk factors for adverse maternal and pregnancy outcomes and to guide therapy and monitoring. Severe disease-related damage, disease activity, and the presence of antiphospholipid and anti-Ro/SS-A and La/SS-B antibodies may all impact prognosis. Knowledge of the safety of certain medications during pregnancy and lactation is still incomplete, but an increasing number of effective rheumatic disease medications can be used during these periods with low risk to maintain stable disease and to improve outcomes for mother and child.